DAMPAK REFORMASI PAJAK TERHADAP PERTUMBUHAN DAN KEPATUHAN UMKM DI ERA UU HPP: TINJAUAN PUSTAKA - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the impact of tax reform through the Tax Harmonisation Law (UU HPP) on the growth and compliance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia using a literature review method. The literature review indicates that tax exemption policies for MSMEs with annual turnover of up to IDR500 million, a reduction in the final income tax rate to 0.5%, and simplification of tax administration and digitalisation have encouraged increased tax compliance and business growth. These reforms provide significant fiscal incentives, simplify reporting, and expand the tax base, enabling MSMEs to allocate more resources to business development. However, challenges remain in terms of tax literacy and administrative readiness, particularly among micro and small MSMEs. Overall, the HPP Law is deemed capable of creating a more inclusive and equitable tax system for MSMEs, although sustained efforts are needed in education and simplifying administrative processes.